Cytotoxicity of 5% ethanol extracts of moringa oleifera leaf as an alternative of root canal irrigant to fibroblast BHK-21 cell culture - Juni J. Nugroho; Aries C. Trilaksana; Nurhayaty Natsir; Christine A. Rovani; Noor Hikmah; Asrianti (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of this study was to determine the cytotoxicity of 5% ethanol extracts of Moringa oleifera leaf based on the percentage of fibroblast cell life after exposure to 5% ethanol extracts of Moringa oleifera leaf.Material and Methods: This study was an experimental laboratory with posttest only control group design. The extract was macerated using ethanol. Toxicity tested using the MTT Assay method. The fibroblast cells distributed in 96 well microplate were divided into 5 treatment groups. Group I as a negative control containing culture media, group II as a positive control containing cells in culture media, group III 5% ethanol extracts of Moringa leaf, group IV 2% chlorhexidine solution and group V 2.5% NaOCl solution. The percentage of cell life is calculated from the optical density value of the ELISA reader. Data were analyzed using the Kruskal Wallis test followed by the Post Hoc test using the Mann Whitney test.Results: The results showed the percentage of life of fibroblast cells after exposure to 5% ethanol extracts of Moringa oleifera leaf = 33.31%, 2.5% NaOCl = 28.89% and 2% chlorhexidine = 39.37% (p = 0.000, p < 0.05).Conclusion: 5% ethanol extracts of Moringa oleifera and 2% chlorhexidine were moderately toxic to fibroblast cells while 2.5% NaOCl was strongly toxic (p = 0.004, p <0.05).